Effect of Ochratoxin A on Body Weight, Feed Intake and Feed Conversion in Broiler Chicken - Sigamani Masilamani Sakthivelan; Ganne Venkata Sudhakar Rao (Veterinary Medicine International)
The effect of ochratoxin A (OA) on the body weight, feed intake, and feed conversion was investigated in broiler chicken fed dietary levels of OA at 0, 1, and 2 ppm for 28 days from hatch. Feeding OA significantly reduced the growth rate of broiler chicken. The reduction was observed from the first week onwards in OA-treated groups. Feed consumption and feed conversion also showed a diminishing trend from the first week of feeding toxin. Its implication on the performance of broiler chicken is discussed.